Legal and Political Analysis of the Red and White Cabinet Reshuffle Based on Good Governance Principles - Mubarok, Rizki (Siyasah Dusturiyah: State Law Review, 2025)
This study examines the design and dynamics of cabinet reshuffles within Indonesia’s presidential system, focusing on the Kabinet Merah Putih under President Prabowo Subianto. The president’s constitutional authority to appoint and dismiss ministers, as stipulated in the 1945 Constitution and the Law on State Ministries, has generated political and legal challenges, particularly due to the influence of the multiparty system and coalition interests. Using a qualitative method with a normative juridical approach, the study finds that cabinet reshuffles are primarily driven by political stabilization rather than performance evaluation. Principles of good governance such as transparency, participation, accountability, and meritocracy have not been fully realized. The amendment through Law No. 61 of 2024, which removes the limit on the number of ministries, further reinforces transactional politics and an oversized cabinet. This research recommends reformulating ministerial evaluation mechanisms based on performance indicators, strengthening meritocratic and technocratic systems in public office appointments, and enhancing civil society oversight to ensure that reshuffles serve as instruments for democratic, effective, and responsive governance.